2009
DOI: 10.1128/jcm.00539-09
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Phenotypic Characteristics of Methicillin-Resistant and Vancomycin-Intermediate Staphylococcus aureus Isolates from Patients with Septic Arthritis

Abstract: Staphylococcus aureus is one of the most common pathogens in community-and hospital-associated infections and frequently causes severe and intractable infections in osteoarticular tissues. S. aureus isolates that are resistant to methicillin (meticillin) (MRSA isolates) and intermediately resistant to vancomycin (VISA isolates) have emerged. In this report, we described two patients, one female and one male, diagnosed with septic arthritis due to S. aureus infections. A total of 13 MRSA isolates were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
3
17
0
2
Order By: Relevance
“…Interestingly, the SCCmec type, spa type, and dru copy numbers of the two vancomycin-intermediate S. aureus (VISA) strains in our previous study were identical to those of the major clones of SCCmec type III-t037-14 and SCCmec type IV-t437-9 found in this study, respectively [28]. This finding is consistent with the result of a previous study, which suggested the clonal dissemination of VISA in a hospital in Taiwan [29].…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, the SCCmec type, spa type, and dru copy numbers of the two vancomycin-intermediate S. aureus (VISA) strains in our previous study were identical to those of the major clones of SCCmec type III-t037-14 and SCCmec type IV-t437-9 found in this study, respectively [28]. This finding is consistent with the result of a previous study, which suggested the clonal dissemination of VISA in a hospital in Taiwan [29].…”
Section: Discussionsupporting
confidence: 83%
“…Given the high incidence of MRSA and the common use of glycopeptides in this region, the emergence of vancomycin‐non‐susceptible strains was not surprising. Fortunately, it appeared that the VISA strains (vancomycin MIC of 4–8 mg/L according to CLSI criteria after 2006) had not disseminated widely in Asian countries, but were identified only sporadically from patients who had previously been exposed to glycopeptides or were on long‐term glycopeptide therapy for persistent staphylococcal infections . In 2003, a nationwide study screening 1000 clinical MRSA isolates from ten hospitals in Taiwan showed only two VISA isolates (0.2%) .…”
Section: Visa Heterogeneous Visa (Hvisa) and Vrsa In Asiamentioning
confidence: 99%
“…It is also the leading cause of skin, [4], [5], cardiovascular tissue [6] and osteoarticular tissue [7] infections, pneumonia [5], [8], and bacteremia [9]. Methicillin-resistant S. aureus (MRSA) has emerged in the 1960s and reached a prevalence of 60–80% in the 1980s [1], [10], [11].…”
Section: Introductionmentioning
confidence: 99%